Formulation Of SnakeheadFish (Channa striata) And Sungkai Leaf (Albertisia papuana Becc) On The Quality OfShredded - Suparno Suparno; Saputera Saputera; Odi Andanu; Wijantri Kusumadati; Arby Saputra Pratama (Agroindustrial Technology Journal, 2023)
This study aims to determine the effect of the formulation of shredded snakehead fish and sungkai leafon the quality of shredded to produce quality shredded. The design of this study used a non-factorial Completely Randomized Design (CRD) with 4 (four) treatments and 6 (six) repetitions, namely: P1 = 100 g snakehead fish; P2= 99 g of snakehead fish: 1.0 g of sungkai leaf powder; P3= 98 g of snakehead fish: 2.0 g of sungkai leaf powder; P4= 97 g of snakehead fish: 3.0 g of sungkai leaf powder. The results of the research on the effect of the formulation of shredded snakehead fish with the addition of sungkai leaf powder on chemical properties showed results that significantly affected ash content 47.37% -5.81%, water content 5.16% -5.66%, protein content 27.36 % -51.21%, fat content 18.06 -22.41%, antioxidant activity 47.81 -103.96 μg/ml, and hedonictests such as color 3.00 -5.44, aroma 4.16 -5 .04, taste 3.96 –5.80 while the texture has no significant effect. The treatment of the formulation of shredded snakehead fish with the addition of sungkai leaves complies with the Indonesian National Standard (SNI)